The pH‐Induced Selectivity Between Cysteine or Histidine Coordinated Heme in an Artificial α‐Helical Metalloprotein. (23rd December 2020) - Koebke, Karl J.; Kühl, Toni; Lojou, Elisabeth; Demeler, Borries; Schoepp‐Cothenet, Barbara; Iranzo, Olga; Pecoraro, Vincent L.; Ivancich, Anabella
Abstract: De Novo metalloprotein design assesses the relationship between metal active site architecture and catalytic reactivity. Herein, we use an α‐helical scaffold to control the iron coordination geometry when a heme cofactor is allowed to bind to either histidine or cysteine ligands, within a single artificial protein. Consequently, we uncovered a reversible pH‐induced switch of the heme axial ligation within this simplified scaffold. Characterization of the specific heme coordination modes was done by using UV/Vis and Electron Paramagnetic Resonance spectroscopies. The penta‐ or hexa‐coordinate thiolate heme (9≤pH≤11) and the penta‐coordinate imidazole heme (6≤pH≤8.5) reproduces well the heme ligation in chloroperoxidases or cyt P450 monooxygenases and peroxidases, respectively. The stability of heme coordination upon ferric/ferrous redox cycling is a crucial property of the construct. At basic pHs, the thiolate mini‐heme protein can catalyze O2 reduction when adsorbed onto a pyrolytic graphite electrode. Abstract : A pH‐dependent preference for the heme ligation is achieved when using self‐assembling α‐helical coiled coils having Cys and His as binding sites. EPR and UV/Vis absorption spectroscopies uncovered a switch in heme axial ligand from His (6≤pH≤8.5) to Cys (9≤pH≤11), mimicking the heme sites in cyt P450 monooxygenase, chloroperoxidase and peroxidases, all three in a single artificial protein.